Model Pelunakan Buah Pisang Raja (Musa sp.) yang Disimpan dalam Atmosfir Termodifikasi - R Hartanto; Suprodjo Suprodjo; Budi Rahardjo; Tranggono Tranggono (agriTECH, 2004)
The banana (Musa sp.) cv. Raja fruits were stored at varied modified atmosphere, in the impermeable cuvettes, containing carbon dioxide concentration of 1, 2, 3, and 4%, oxygen concentration of 2, 4, 6, and 8% and nitrogen. The temperature treatments were 12, 20, and 24 C. The gas within the cuvette was replaced daily. The texture of the fruit was measured every two day. The model of textural behavior was developed The results showed that the model of textural behavior was fit to predict the banana texture stored in the modified atmosphere condition.